The potential biomarker value of soluble CD36 in the treatment of diabetic kidney disease: evidence from GLP-1 and insulin interventions - Li, Wenxuan; Wang, Yangang (Frontiers in Endocrinology, 2025)
BackgroundSoluble CD36 (sCD36), the circulating form of the scavenger receptor CD36, plays a key role in lipid accumulation and inflammation during the progression of diabetic kidney disease (DKD), and has been proposed as a promising non-invasive biomarker. The renoprotective effects of glucagon-like peptide-1 receptor agonists (GLP-1RAs) may involve modulation of sCD36. This study aimed to evaluate the impact of GLP-1RA and insulin treatment on sCD36 levels and their association with renal function in DKD patients.MethodsThis single-center, prospective observational cohort study enrolled 191 patients with type 2 diabetes and early-stage DKD, who were stratified into three groups based on treatment regimen: control group (n = 63), insulin group (n = 71), and GLP-1RA group (n = 57). All patients received standard care with metformin, with the insulin and GLP-1RA groups receiving additional respective treatments for 12 weeks. Clinical parameters including sCD36, urinary albumin-to-creatinine ratio (UACR), lipid profile, glycemic markers, and islet function indices were assessed at baseline and post-treatment. Intra- and inter-group comparisons were performed using paired tests and analysis of covariance. Generalized linear regression models were applied to assess the relationship between sCD36 and renal function.ResultsBaseline sCD36 and UACR levels were comparable across the three groups (P > 0.05). After 12 weeks, sCD36 levels significantly declined in the GLP-1RA group (median: 195.20 ng/mL, IQR: 160.45–314.75), compared to the insulin group (364.60 ng/mL, IQR: 279.10–394.10) and control group (386.10 ng/mL, IQR: 323.60–471.30) (P < 0.001). The GLP-1RA group also showed the most marked reduction in UACR (P < 0.001). Regression analysis demonstrated a significant positive association between sCD36 and UACR levels both before and after treatment (P < 0.001), and the change in sCD36 (ΔsCD36) was positively correlated with the improvement in UACR, suggesting a link to reduced renal lipotoxicity and inflammation.ConclusionGLP-1RAs significantly reduce sCD36 and UACR levels in patients with early DKD, outperforming insulin in renoprotection. These findings raise the possibility that GLP-1RAs may exert renoprotective effects through modulation of CD36-related pathways, although direct mechanistic validation was not performed in this study.sCD36 may serve as a useful biomarker for monitoring DKD progression and therapeutic response, though further multicenter and long-term studies are needed to confirm its clinical utility.